Site-selective Cp*Rh(iii)-catalyzed C–H amination of indolines with anthranils. Issue 2 (2nd December 2016) - Mishra, Neeraj Kumar; Jeon, Mijin; Oh, Yongguk; Jo, Hyeim; Park, Jihye; Han, Sangil; Sharma, Satyasheel; Han, Sang Hoon; Jung, Young Hoon; Kim, In Su
Abstract : The pyrimidinyl-directed C–H functionalization of indolines with anthranils as amination sources under rhodium(iii ) catalysis is described to afford a range of C7-aminated indoline derivatives with excellent site-selectivity and functional group compatibility. Abstract : The pyrimidinyl-directed C–H functionalization of indolines with anthranils as amination sources under rhodium(iii ) catalysis is described. This transformation efficiently provides a range of C7-aminated indoline derivatives with excellent site-selectivity and functional group compatibility. The resulting framework containing amino and carbonyl groups provides facile access to an important synthetic building block, which can be readily converted to biologically interesting heterocycles.